2021
DOI: 10.52380/ijpes.2021.8.2.500
|View full text |Cite
|
Sign up to set email alerts
|

Science Teachers’ Argument Types and Supporting Reasons on Socioscientific Issues: Covid-19 Issue

Abstract: This study examines the types of arguments and supporting reasons of science teachers on socioscientific issues. The case study was used in this study conducted with seven science teachers. Data were collected through three scenarios developed about vaccination, curfew and distance education in the context of COVID-19. Within the context of the data obtained, the argument types of the teachers were evaluated through the deductive content analysis, and the supporting reasons they presented for their arguments w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 2 publications
(2 reference statements)
2
8
0
1
Order By: Relevance
“…They finetune a Bart-large model (Lewis et al, 2020) to automatically identify the stance. One more dataset related to the COVID-19 pandemic is collected by seven science teachers through three scenarios (Atabey, 2021). This dataset contains not only stances about vaccination, curfew and distance education, but also arguments and supporting reasons that might construct an argument mining dataset.…”
Section: Previous Workmentioning
confidence: 99%

RuArg-2022: Argument Mining Evaluation

Kotelnikov,
Loukachevitch,
Nikishina
et al. 2022
Preprint
“…They finetune a Bart-large model (Lewis et al, 2020) to automatically identify the stance. One more dataset related to the COVID-19 pandemic is collected by seven science teachers through three scenarios (Atabey, 2021). This dataset contains not only stances about vaccination, curfew and distance education, but also arguments and supporting reasons that might construct an argument mining dataset.…”
Section: Previous Workmentioning
confidence: 99%

RuArg-2022: Argument Mining Evaluation

Kotelnikov,
Loukachevitch,
Nikishina
et al. 2022
Preprint
“…Despite of an advanced development of medical knowledge and technology as well as health services, many diseases occur and potentially threat our quality of life. As a contemporary instance, covid-19 pandemic which caused by SARS Co-2 virus has been has a significant impact to all of us globally, not only for health condition, but also toward life aspects we live in, such as economics and education activity (Atabey, 2021). It is an interesting to view that dealing with health issues caused such by covid-19, some people may apply their scientific knowledge and have a well-informed perspective as well as decision to respond it.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the state of health issue related to covid-19 above described, it is clearly viewed that the issue can be defined as one of socio-scientific issues (SSI) (Atabey, 2021;Grace & Bay, 2011). SSI represent issues where scientific knowledge and socio-cultural dimensions are interrelated and presenting conflicts or dilemma faced by society and lead to multiperspectives confrontation amongst individuals (Sadler, 2011;Zeidler & Nichols, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Atabey (2021) reported that a middle school science teacher used argumentation to introduce topics related to COVID-19 such as vaccines and distant education.…”
Section: Teaching Of Covid-19 Pandemic In Middle Schoolmentioning
confidence: 99%
“…Any field could address a real-world problem, yet the use of active learning activities including SSIs is significant in immunology. In the Immunology context, debates about COVID-19 vaccination are among the "hottest" controversies nowadays (Atabey, 2021). Upon teaching COVID-19 pandemic in a science classroom, students gained the opportunity to use their scientific knowledge and evidence to engage in arguments which allowed them to take reasonable and effective democratic decisionmaking solutions (Davisson, 2019;Lindahl et al, 2019).…”
Section: Teaching Of Covid-19 Pandemic In Immunologymentioning
confidence: 99%